From Fresh to Dried: Evaluating Drying Kinetics of Sultana and Besni Grapes - Mehmet Başlar (International Journal of Gastronomy Research)
This research investigates the thin-layer drying kinetics of Sultana and Besni grapes using the forced-air drying method. The study evaluates the applicability of three drying models (Lewis, Page, and Henderson & Pabis) to the experimental data and concurrently determines the effective moisture diffusivity and activation energy of dried grapes at varying temperatures. The grapes were dried at different temperatures (55, 65, and 75 °C) in an air-forced drying oven until a moisture ratio of 0.14 ± 0.01 kg water/kg dry matter was achieved. When evaluating the coefficient of determination (R2), chi-square (χ2), and root-mean-square error (RMSE) values for the dehydrated grapes, the results reveal that all three models provided a reasonable fit for the experimental data, with the Page model proving to be the best fit. Effective moisture diffusivity values increased significantly with rising temperatures, and higher temperatures accelerate the drying process. The conclusions drawn from the study underscore the importance of understanding grape-specific drying kinetics for improving energy efficiency and optimizing drying procedures. The Page model has been highlighted as particularly useful for future studies and industrial applications. This study provides valuable insights into both the academic community and the food industry, suggesting potential pathways for energy conservation and enhanced drying processes in dehydrated foods.